2015
DOI: 10.1097/igc.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Increased Association Between Endometriosis and Endometrial Cancer

Abstract: ObjectiveAssociation between endometriosis and ovarian cancer has been well established. Nonetheless, endometriosis may also be associated with endometrial cancer because of shared etiological mechanisms of both estrogen stimulation and chronic inflammation; however, the association between these 2 disorders has rarely been investigated.MethodsThe National Health Insurance Research Databases in Taiwan were retrieved and analyzed. The case cohort consisted of patients with a diagnosis of endometriosis between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
(30 reference statements)
1
46
0
2
Order By: Relevance
“…Since then, numerous studies have demonstrated the overlap of definition criteria of malignant phenotype with those of endometriosis. Results of meta-analyses revealed their increased association [204,205].…”
Section: Relationships Between Endometriosis and Malignancymentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, numerous studies have demonstrated the overlap of definition criteria of malignant phenotype with those of endometriosis. Results of meta-analyses revealed their increased association [204,205].…”
Section: Relationships Between Endometriosis and Malignancymentioning
confidence: 99%
“…The significance of borderline tumors is currently regarded as a part of endometriosis-associated ovarian carcinoma spectrum [206,214,215]. Moreover, recent evidences indicate that patients with endometriosis have a significant risk for endometrial cancer, mainly endometrioid and clear cell subtypes [220].…”
Section: Relationships Between Endometriosis and Malignancymentioning
confidence: 99%
“…Nearly 30% of the simultaneous cases were reported to harbor endometriosis. [4][5][6] Both endometriosis and endometrial cancer have the same origin; they have an identical molecular profile and etiological mechanisms such as chronic inflammation and the estrogen effect. Therefore, it is possible that endometriosis might affect the risk and prognosis of endometrial cancer.…”
mentioning
confidence: 99%
“…Therefore, it is possible that endometriosis might affect the risk and prognosis of endometrial cancer. 4,[7][8][9] Despite these facts, due attention has not been given to the endometriosis-endometrial cancer association. To the best of our knowledge, no study in the literature has discussed the impact of endometriosis on the prognosis of endometrial cancer.…”
mentioning
confidence: 99%
“…The pathogenesis of ovarian cancer is complex, and is affected by numerous epigenetic and genetic factors (2). Endometriosis is usually a benign disorder, but is associated with an increased risk for developing ovarian (3) and endometrial cancers (4). Endometrioid and clear cell carcinoma of the ovary (endometriosis-associated ovarian cancer, EAOC) originates from endometriosis.…”
Section: Introductionmentioning
confidence: 99%